Daunorubicin and gambogic acid coloaded cysteamine-CdTe quantum dots minimizing the multidrug resistance of lymphoma in vitro and in vivo - Zhou Y; Wang R; Chen B; Sun D; Hu Y; Xu P (International Journal of Nanomedicine, 2016)
Yi Zhou,1,2 Ruju Wang,1 Bing Chen,1 Dan Sun,3 Yong Hu,2 Peipei Xu1 1Department of Hematology, Drum Tower Hospital, School of Medicine, 2Institute of Materials Engineering and Collaborative Innovation Center of Chemistry for Life Sciences, College of Engineering and Applied Sciences, Nanjing University, Nanjing People’s Republic of China; 3School of Mechanical Engineering, Queen’s University Belfast, Belfast, UK Abstract: To minimize the side effects and the multidrug resistance (MDR) arising from daunorubicin (DNR) treatment of malignant lymphoma, a chemotherapy formulation of cysteamine-modified cadmium tellurium (Cys-CdTe) quantum dots coloaded with DNR and gambogic acid (GA) nanoparticles (DNR-GA-Cys-CdTe NPs) was developed. The physical property, drug-loading efficiency and drug release behavior of these DNR-GA-Cys-CdTe NPs were evaluated, and their cytotoxicity was explored by 3-[4,5-dimethylthiazol-2-y1]-2,5-diphenyltetrazolium bromide assay. These DNR-GA-Cys-CdTe NPs possessed a pH-responsive behavior, and displayed a dose-dependent antiproliferative activity on multidrug-resistant lymphoma Raji/DNR cells. The accumulation of DNR inside the cells, revealed by flow cytometry assay, and the down-regulated expression of P-glycoprotein inside the Raji/DNR cells measured by Western blotting assay indicated that these DNR-GA-Cys-CdTe NPs could minimize the MDR of Raji/DNR cells. This multidrug delivery system would be a promising strategy for minimizing MDR against the lymphoma. Keywords: daunorubicin, gambogic acid, Cys-CdTe QDs, multidrug resistance, non-Hodgkin’s lymphoma